Correlations between Campaign Message and Exposure, and Behavioral Change: The Case of Cinema 21‘s #PadaTempatnya Public Relations Campaign - Muhammad Jordan Valentino Rickardo; Deborah N. Simorangkir (ADI Publisher, 2020)
Cinema 21 created #PadaTempatnya campaign to change people's lifestyles to be more concerned with cleanliness, especially in the cinema after watching a movie. The purpose of this study was to find out if there is a correlation between the #Padatempatnya campaign message and exposure and audience behavioral change to dispose of trash in its place. A survey of 115 young adults ages 20 to 24 years old was conducted. A Spearman Correlation Test found that there was a significant moderate positive correlation between campaign exposure, and significant strong positive correlation between campaign messages and behavioral change to dispose of trash in its place. Data was also analyzed using the perspective of the AIDA model. Findings showed that this campaign was most effective in the Attention stage.